Social Construction of Sharia Investment Among Millennial Muslims in Makassar: An Ethnographic Study - Amin, Andi Mustika (Malaqbi Publisher, 2025)
This ethnographic study explores how millennial Muslims in Makassar construct their understanding and practice of Sharia-compliant investment through social processes and community interactions. Using participant observation, in-depth interviews, and focus group discussions with 32 participants across five investment communities, the research reveals three distinct pathways of knowledge construction: scholarly consultation, peer learning, and personal interpretation. The findings demonstrate that millennial Muslim investors actively negotiate religious principles with contemporary financial realities through collective deliberation processes, creating hybrid forms of